Upaya Mengurangi Prokrastinasi Akademik Siswa Kelas VIII menggunakan Layanan Bimbingan Kelompok dengan Teknik Self-Management di SMP Negeri 10 Kota Jambi - Siti Amanah; Ari Lisnawati (Journal on Education, 2023)
Academic procrastination is the tendency to delay assignments by doing other things that are considered more enjoyable and done on purpose so that assignments are not completed. Based on the results of researchers' observations on December 12 2021 at SMP Negeri 10 Jambi City class VIII, 10 students were found to be experiencing academic procrastination. Using self-management techniques in group guidance services can reduce academic procrastination behavior that students experience. The purpose of this research is to reduce students' academic procrastination using group guidance services using self-management techniques at SMP Negeri 10 Jambi City. This type of research is service action research (PTL). Sampling criteria (research subjects) namely purposive sampling with a total of 10 class VIII people. This research was conducted in 3 cycles and each cycle consisted of 1 action and this research consisted of four competencies for each cycle, namely planning, implementing, evaluating, and reflecting. The results of this study indicate that students' academic procrastination can be reduced by using self-management techniques. From the results of the initial questionnaire before the implementation of the cycle, a percentage of 91.8% was obtained and the final questionnaire after completing cycle III obtained a percentage of 44.6%. These results indicate a reduction in academic procrastination in students. While the results of the observation per cycle percentage obtained: Cycle I overall percentage was 46%, cycle II was obtained with a percentage of 64%, cycle III was 88%. These results indicate that there are positive changes in students and the results of this study are expected to help counseling teachers in improving students' low prosocial behavior in the aspects of sharing, cooperation, helping, donating and honesty.